A new species of Hippomonavella (Bryozoa: Cheilostomata) from the Holocene and Recent of Argentina and Uruguay (Southwest Atlantic) - López-Gappa, J.; Liuzzi, M.g.; Pereyra, C. (Zootaxa, 2020)
Hippomonavella charrua n. sp. is introduced based on material from the continental shelf off Uruguay. Bilaminar fragments of this species were also found in mid-Holocene deposits of Destacamento Río Salado Member, Canal de las Escobas Formation (Buenos Aires Province, Argentina), ca. 6,000 yr BP. Hippomonavella charrua n. sp. resembles H. brasiliensis Ramalho, Muricy & Taylor, 2008, but differs from this species in its more triangular and protruding avicularia occurring in just a small proportion of zooids. Hippomonavella charrua n. sp. is the third species of the genus with both fossil and Recent representatives. The tatiform ancestrula and the early astogeny are described for the first time in a species of Hippomonavella.